2003
DOI: 10.1177/1356336x030093003
|View full text |Cite
|
Sign up to set email alerts
|

A Changing Culture? Interrogating the Dynamics of Peer Affiliations Over the Course of a Sport Education Season

Abstract: This article focuses on the effects of pupils' social involvement goals and the peer culture on behaviour and participation in physical education (PE). The extent to which sport education (SE) disrupted peer power relations and reconfigured dominant social groupings is examined and the potential of SE to establish a culture in PE where pupils of both genders value participation in PE and sport is discussed. The article draws on data gathered during a seven-month case study with Year 7 pupils (age 11-13 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 14 publications
5
27
0
2
Order By: Relevance
“…Relativamente à investigação centrada na perceção de professores e alunos sobre o desenvolvimento de experiências pedagógicas em unidades de MED, esta tem demonstrado o reconhecimento de ambos os atores no elevado impacto educacional deste modelo, nomeadamente na aprendizagem (Browne, Carlson, & Hastie, 2004;Hastie & Sinelnikov, 2006), no desenvolvimento pessoal e social dos alunos (Grant, 1992;Pill, 2008), nas suas atitudes (Hastie & Sinelnikov, 2006;MacPhail, Gorely, Kirk, & Kinchin, 2008) e valores (Bennet & Hastie, 1997;O'Donovan, 2003). Todavia, esta investigação tem sido quase exclusivamente focada nos desportos de equipa, tais como o Futebol, o Basquetebol e o Voleibol (Hastie, Martinez de Ojeda, & Calderón, 2011).…”
unclassified
“…Relativamente à investigação centrada na perceção de professores e alunos sobre o desenvolvimento de experiências pedagógicas em unidades de MED, esta tem demonstrado o reconhecimento de ambos os atores no elevado impacto educacional deste modelo, nomeadamente na aprendizagem (Browne, Carlson, & Hastie, 2004;Hastie & Sinelnikov, 2006), no desenvolvimento pessoal e social dos alunos (Grant, 1992;Pill, 2008), nas suas atitudes (Hastie & Sinelnikov, 2006;MacPhail, Gorely, Kirk, & Kinchin, 2008) e valores (Bennet & Hastie, 1997;O'Donovan, 2003). Todavia, esta investigação tem sido quase exclusivamente focada nos desportos de equipa, tais como o Futebol, o Basquetebol e o Voleibol (Hastie, Martinez de Ojeda, & Calderón, 2011).…”
unclassified
“…He contrasted the values and practices of the community of practice of PE with the values and practices of the community of practice of computer gamers, which he wanted to be part of. That the incompatibility of identities can restrict participation in PE is confirmed by studies showing that some girls feel caught between the values of feminism and the values of masculinity in PE (Cockburn & Clark, 2002;With-Nielsen & Pfister, 2011;O'Donovan, 2003).…”
Section: Field 4: Participation Without Meaningfulness and Legitimacymentioning
confidence: 59%
“…So the relations between the girls and between Michael and the girls hamper Michael's participation, placing him in a peripheral position (upper corner field 2, Figure 2) and at risk of being marginalised (lower corner field 2, Figure 2) in this specific case. The significance of social relations or popularity among peers has also been reported in studies by Hills (2007), Grimminger (2013) and O'Donovan (2003). Hills (2007) found that girls' physical skills, as well as girls' social relationships, were important in shaping their involvement in PE and for the power relations between the included and the excluded students.…”
Section: We Give Them the Ball But They Give It Back To Us Straight mentioning
confidence: 85%
See 2 more Smart Citations